Effect of contact stress on fretting fatigue behaviour of 35CrMoA steel under multiaxial nonproportional paths. Issue 1 (18th October 2020) - Zhou, Zhiqiang; Liu, Xiaoshan; He, Guoqiu; Ge, Bin; Le, Peiwen; Li, Jingquan; Pan, Jiaqi; Yang, Yang
Abstract: Fretting fatigue often occurs in contact couples subjected to both bulk oscillatory loads and normal loads, which accelerates the initiation and propagation of fatigue cracks. This study explores the multiaxial fretting fatigue behaviour of 35CrMoA steel with different contact stresses under diamond and square loading paths by experimental methods. From experimental results, the fracture mechanisms with the increase of contact stress have been summarized by combining the analysis of macrorupture and microrupture surface. The strain response behaviour, characteristics of fretting region and crack propagation direction are also analysed and concluded considering the influence of loading path and contact stress in this paper, which have been rarely mentioned in the previous literature. In addition, debris composition of stick and slip regions is investigated as well.